Diario de un ama de casa desquiciada - Kaufman, Sue, 1926-1977; Busquets, Milena; Kaufman, Sue, 1926-1977. (Barcelona, España : Libros del Asteroide S.L.U., 2013)
Story of harried New York wife finding much needed release via an affair with a self-centered creep.
Online resource; title from ePub title page (Digitalia, viewed March 20, 2018)
Keywords: Housewives -- New York (State) -- New York -- Fiction; Man-woman relationships -- Fiction; Diary fiction; Electronic books